Elmo's magical unicorn - Webster, Christy; Lew, Steph (New York, NY: Random House Children's Books, a division of Penguin Random House LLC, 2021)
Elmo has a magical visit with a unicorn in this fantastical Sesame Street board book! Elmo really wants to meet a unicorn. Luckily, his magical friend, Abby Cadabby, is able to make Elmo's dream come true. Soon Elmo and the unicorn are jumping over clouds, sliding down rainbows, and playing amazing games with his other Muppet friends. But will the unicorn feel at home on Sesame Street? Boys and girls will love this Sesame Street board book with sturdy pages! Sesame Workshop, the nonprofit educational organization behind Sesame Street, aims to help kids grow smarter, stronger, and kinder through its many unique domestic and international initiatives. These projects cover a wide array of topics for families around the world.
Cover title.
On board pages.
Keywords: Magic -- Juvenile fiction; Unicorns -- Juvenile fiction; Board books; Unicorns -- Fiction; Magic -- Fiction; Board books